The Influence of Influencer Credibility and Brand Image on Interest in Buying Facial Skin Care Products Marketed via TikTok among Generation Z Female Consumers in Denpasar City - DEWI, I Gusti Ayu Agung Istri Sari; PUTRI, Sukmasari Triana Gita (Journal of Tourism Economics and Policy, 2025)
The rise of social media, especially TikTok, has transformed how companies market their products, particularly in the beauty industry. Influencers are often used as an effective marketing strategy as they can shape consumer perception and purchasing decisions, especially among Generation Z who are active on TikTok. This study aims to determine the influence of influencer credibility and brand image on the purchase intention of facial skin care products marketed through TikTok, focusing on female Generation Z consumers in Denpasar City. This is a quantitative associative research using 107 respondents. The data were analyzed using multiple linear regression. The results indicate that the influencer credibility variable (X1) and the brand image variable (X2) significantly influence the purchase intention (Y) of facial skin care products marketed through TikTok among Generation Z female consumers in Denpasar.